Academic Self-Concept and Mathematical Computation on Geometric Sequences and Series: The Confirmatory Factor Analysis - Asya Khaula Aziza; Rika Mulyati Mustika Sari; Rafiq Zulkarnaen (SJME (Supremum Journal of Mathematics Education), 2026)
The purpose of this study was to investigate the relationship between academic self-concept and mathematical computation in the field of geometry, particularly on geometric sequences and series. This study employed a quantitative correlational design using Confirmatory Factor Analysis (CFA). Data were collected through a mathematical computation test consisting of eight essay items and an academic self-concept questionnaire administered to 200 senior high school students in Bogor Regency. The results indicated a good model fit, as reflected by the fit indices (CFI = 0.994, TLI = 0.992, and RMSEA = 0.0463). Academic self-concept was significantly associated with mathematical computation, with a correlation coefficient of 0.37. The mathematical computation construct demonstrated strong reliability and validity (CA = 0.923, CR = 0.929, AVE = 0.781), with abstraction as the most dominant factor (0.917). Meanwhile, the academic self-concept construct showed CA = 0.968, CR = 0.977, and AVE = 0.889, with self-confidence identified as the most dominant factor (0.964). These findings indicate that students’ self-confidence plays a crucial role in supporting abstraction in mathematical computation. Therefore, it is recommended that mathematics instruction should emphasize learning activities that strengthen students’ academic self-confidence and promote abstraction skills to improve mathematical problem-solving performance.